Apple in the Pagan Culture of Georgians and Other Peoples - Makashvili, Malkhaz ("Intercultural Dialogues" Transactions, 2025)
This article presents the symbolism of the apple in the folklore of various nations, including Georgians, and discusses its connection with people's beliefs, ideas, and customs. The customs, myths, and legends of Georgians, Yezidis, Britons, Romans, Phrygians, Indians, ancient Greeks, Kyrgyz, Persians, Russians et cetera, information preserved in the Old Testament, ancient Hebrew Haggadah and medieval, ancient Greek and Jewish poetry is analyzed. The article discusses two opinions. According to one suggestion, an apple appears in folk beliefs and customs by chance, not as an apple as particular plant species, but as an abstact fruit, symbolizing fertility and abundance. Based on a comparative analysis of the data, presented in the current artikle, we advocate opposite suggestion, that apple does not appear by chance, but rather plays its specific simbolic role in the beliefs, customs, and myths of various nations, including Georgians.